2015
DOI: 10.1001/jama.2015.3656
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Reporting Items for a Systematic Review and Meta-analysis of Individual Participant Data

Abstract: IMPORTANCE Systematic reviews and meta-analyses of individual participant data (IPD) aim to collect, check, and reanalyze individual-level data from all studies addressing a particular research question and are therefore considered a gold standard approach to evidence synthesis. They are likely to be used with increasing frequency as current initiatives to share clinical trial data gain momentum and may be particularly important in reviewing controversial therapeutic areas. OBJECTIVE To develop PRISMA-IPD as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
1,197
0
15

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,624 publications
(1,277 citation statements)
references
References 37 publications
7
1,197
0
15
Order By: Relevance
“…Trialists should register their studies [49e51] and consult the EQUATOR Network [52] for relevant reporting guidelines for protocols [28] and research reports [26]. Systematic reviewers should use reporting guidelines when publishing protocols [53] and final reports using aggregate data [54] or IPD [55]. Our results demonstrate that such efforts could reduce opportunities for cherrypicking.…”
Section: Discussionmentioning
confidence: 92%
“…Trialists should register their studies [49e51] and consult the EQUATOR Network [52] for relevant reporting guidelines for protocols [28] and research reports [26]. Systematic reviewers should use reporting guidelines when publishing protocols [53] and final reports using aggregate data [54] or IPD [55]. Our results demonstrate that such efforts could reduce opportunities for cherrypicking.…”
Section: Discussionmentioning
confidence: 92%
“…This report was prepared according to the Preferred Reporting Items for Systematic reviews and MetaAnalyses (PRISMA) IPD guidance (14) and prospectively registered with Clinicaltrials.gov (NCT0083244) and the PROSPERO database of systematic reviews (CRD42014010012). (15) Detailed rationale and methods have previously been published.…”
Section: Methodsmentioning
confidence: 99%
“…Results on secondary outcomes, namely depressive symptoms and insight/delusionality, should especially be interpreted with caution as they were based on reports in five and four studies, respectively. Given the relatively small sample, future metaanalyses of individual participant data may be helpful to further increase power and better control for potential confounds (Stewart et al, 2015). Finally, several studies failed to report on the ethnic background of their participants; over 80% of patients included in the trials that reported this information were from White backgrounds and, thus, it is unclear whether CBT is equally acceptable and efficacious in patients from ethnic minorities.…”
Section: Cognitive-behavioral Therapy For Body Dysmorphic Disorder 18mentioning
confidence: 99%